2001
DOI: 10.1590/s0101-81752001000100022
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion of Stramonita haemastoma (Linnaeus) (Gastropoda, Muricidae) on a mixed shore of rocks and sand

Abstract: ABSTRACT. Mixed shores of rocks and sand are appropriate systems for the study of limitations that the isolation of rocks may impose for gastropods that typically inhabit rocky shores. We marked 52 Slramoll;la haemasloma (Linnaeus, 1767) snails on a mixed shore and found that 34 of them moved between rocks one to four times during 15 surveys in a period of 72 days. In the experiments, the snails moved on rock by continuous, direct, ditaxic, alternate undulations of the toot sole but on submerged sand they use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Most benthic marine invertebrates are sessile or slow‐moving as adults, such that adult dispersal cannot possibly explain these apparent range extensions. For example, based on locomotion rates and movement patterns for rocky‐shore gastropods (Miller 1974; Palmer 1980; Papp & Duark 2001) a range extension of 1000 km by species lacking planktonic larvae could take millions of years.…”
Section: Introductionmentioning
confidence: 99%
“…Most benthic marine invertebrates are sessile or slow‐moving as adults, such that adult dispersal cannot possibly explain these apparent range extensions. For example, based on locomotion rates and movement patterns for rocky‐shore gastropods (Miller 1974; Palmer 1980; Papp & Duark 2001) a range extension of 1000 km by species lacking planktonic larvae could take millions of years.…”
Section: Introductionmentioning
confidence: 99%
“…These authors showed that the dorsal surface of the shell, mainly in the proximity of the apex, was generally more fouled by epibiotic polychaetes than the ventral surface, a pattern of colonization which is in agreement with the present results and that is probably related to the mode of locomotion of this snail. Indeed, it has been shown that S. haemastoma moves by crawling on hard substrate and by burrowing on soft substrate when the rocks become exposed during low tides (Papp and Duarte 2001). In both cases, the continuous abrasion of the ventral surface leads to an erosion of the settled epibionts, with the same finding being also recorded in H. trunculus (Vasconcelos et al 2007).…”
Section: Discussionmentioning
confidence: 68%